Bees : A Natural History - O'Toole, Christopher; Ross, Edward (New York : Firefly Books, 2013)
INSECTS & SPIDERS. Only recently have biologists discovered that human survival is inextricably linked to the survival of insects, specifically, bees. Today the 16-20,000 species of bee continue to play vital roles in human ecology. We survive only by grace of the life-sustaining network of bee-plant relationships. Bees immerses readers in the world of Apinae whose diversity of form and behaviour is eloquent testimony to the fine-tuning of natural selection.
A Peter N. Nevraumont book.
Includes bibliographical references and index.
Keywords: Bees; Bees -- Pictorial works